(untitled) (Gestão & Regionalidade, 2019)
This study investigates the relationship between the collective entrepreneurial actions in specific territories and the creation of social innovation. This is an empirical qualitative study, based on case study method. Social actors were interviewed and data were analyzed through NVivoÂ© software. The findings indicate that social innovation process is related to the collective local dwelling mode and to the social and economic context. The study identifies positive and negative aspects of territorial development process through the collective entrepreneurial actions. The six theoretical elements model built is original and proposes one contribution to territorial development and social innovation emergence.